2019
DOI: 10.22434/ifamr2018.0073
|View full text |Cite
|
Sign up to set email alerts
|

Exploring retailer marketing strategies for value added bean products in Kenya

Abstract: Unlike many other Sub-Saharan African countries, for many years Kenya had comparative advantages in the manufacturing of processed bean products. However, for new competitors intending to join the bean processing industry, little is known about marketing strategies for value added bean products. Using data from 90 retailers in the Nairobi and Kiambu counties in Kenya, a two-step econometric procedure-multivariate probit and Poisson regression models were applied to analyse retailers’ marketing strategy decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…While beans are traditionally sold as dry seeds to consumers in Eastern and Southern Africa, the development of food processing infrastructure and demand for convenience foods is increasing the market potential for canned beans (Nakazi et al, 2019). Canning quality of bean genotypes is a complex trait that is determined by many factors, such as hydration characteristics of seed, cooking requirements, and consumer and processor preferences (Posa-Macallincag et al, 2002).…”
mentioning
confidence: 99%
“…While beans are traditionally sold as dry seeds to consumers in Eastern and Southern Africa, the development of food processing infrastructure and demand for convenience foods is increasing the market potential for canned beans (Nakazi et al, 2019). Canning quality of bean genotypes is a complex trait that is determined by many factors, such as hydration characteristics of seed, cooking requirements, and consumer and processor preferences (Posa-Macallincag et al, 2002).…”
mentioning
confidence: 99%
“…A study of processed beans products in Kenya found that the retail price of canned and chilled/frozen beans was approximately 2.5 times the price of sorted and packed beans [17], and this will be higher than the price of loose beans typically bought at local markets. Ugen et al [13] also found that the retail price of canned beans imported to Uganda was three times higher than the price of unprocessed dried beans.…”
Section: High Pricesmentioning
confidence: 98%
“…Given that the majority of consumers for processed bean products (in Kenya) are individuals with limited access to information on specific products, it is important that retailers use various information channels to reach out to targeted consumers [17]. Although neither a producer nor a retailer, ICRISAT are investing in a range of initiatives aimed at addressing awareness and knowledge gaps, such as reality TV shows, competitions, village level demonstrations, etc.…”
Section: Lack Of Information and Knowledge On How To Cookmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on the strategic business decisions of food retailers are from Europe (Insch et al, 2011;Liu et al, 2013;Blunch, 2001, 2008) and Asia (Lin and Wu, 2011;Manjeshwar et al, 2013;Skallerud and Grønhaug, 2010). Other empirical studies on the business decisions of traditional food retailers in SSA have focused on marketing decisions (Nakazi et al, 2019;Yami et al, 2020) and technology adoption behaviour (Kamrath et al, 2018), but there is limited empirical evidence on strategic business decisions. Although Nandonde and Kuada (2016) used a qualitative approach to evaluate the purchasing behaviour of modern food retailers in Tanzania, they did not investigate the factors that influence retailers' decisions on the quantity of products purchased and procurement strategy.…”
Section: Introductionmentioning
confidence: 99%